ORAL SECONDARY INFECTION IN STEVENS-JOHNSON SYNDROME PATIENT WITH ORAL INVOLVEMENT: A CASE REPORT - Etis Duhita Rahayuningtyas; Indah Suasani Wahyuni; Irna Sufiawati (FKG Unlam, 2021)
ABSTRACTBackground: Stevens-Johnson syndrome (SSJ) is a hypersensitivity reaction that is often triggered by drugs but this case is rare. These reactions result in uncontrolled keratinocyte damage to the skin and mucosa throughout the body, including the oral mucosa, and are often life-threatening. The use of high doses of corticosteroids is a treatment that is often given but it can trigger secondary infections of fungal and viral in the oral cavity. Purpose: This case report discusses the management of oral manifestations and secondary infections in SSJ patients, and becomes guidance for health professionals. Case: A-42-years-old male patient was consulted from the Department of Dermatology and Venereology (DV) due to oral pain and eating difficulties. The severity-of-illness-score for toxic-epidermal-necrolysis (SCORTEN) was 1. Erosive serosanguinous crusts, tend to bleed were found on the lips. Intraoral clinically presented wide erosive lesions and multiple ulcers, accompanied by a pseudomembranous plaque, and teeth decay. Hematologic examination showed an increase in leukocytes, neutrophil segments, monocytes, SGOT, urea, and creatinine as well as decreased hemoglobin, hematocrit, erythrocytes, MCHC, protein, and albumin. Anti-HSV1 IgG increased almost 6 times than normal values. The patient was diagnosed with SJS with oral involvement, secondary infections of pseudomembranous candidiasis, and herpetic stomatitis. Case Management: Systemic therapy given were intravenous dexamethasone, ranitidine, calcium, and cetirizine, from the DV Department, while hydrocortisone lip ointment, Chlorhexidine digluconate 0.12%, and Nystatin oral suspension for oral problems. The lesions progressed in 24 days. Conclusion: Oral secondary infections may occur in SJS patients due to high-dose corticosteroid therapy.Keywords: Herpetic Stomatitis, Oral Manifestation, Oral Secondary Infection, Pseudomembranous Candidiasis, Stevens-Johnson Syndrome.